+0  
 
0
153
1
avatar

If g(x) = -2x^2-3. Find g(0).

Guest Jun 24, 2017
edited by Guest  Jun 24, 2017

Best Answer 

 #1
avatar+5573 
+2

g(x)   =  -2x2 - 3                 To find  g(0)  , replace every instance of  " x "  with  " 0 "  .

 

g(0)  =  -2(0)2 - 3                (0)2  =  0

 

g(0)  =  -2(0) - 3                 -2(0)  =  0

 

g(0)  =  0 - 3

 

g(0)  =  -3

hectictar  Jun 24, 2017
Sort: 

1+0 Answers

 #1
avatar+5573 
+2
Best Answer

g(x)   =  -2x2 - 3                 To find  g(0)  , replace every instance of  " x "  with  " 0 "  .

 

g(0)  =  -2(0)2 - 3                (0)2  =  0

 

g(0)  =  -2(0) - 3                 -2(0)  =  0

 

g(0)  =  0 - 3

 

g(0)  =  -3

hectictar  Jun 24, 2017

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details